A Light Incident Angle Switchable ZnO Nanorod Memristor: Reversible Switching Behavior Between Two Non‐Volatile Memory Devices. (1st September 2013) - Park, Jinjoo; Lee, Seunghyup; Lee, Junghan; Yong, Kijung
<x xml:space="preserve">Abstract</x> A light incident angle selectivity of a memory device is demonstrated. As a model system, the ZnO resistive switching device has been selected. Electrical signal is reversibly switched between memristor and resistor behaviors by modulating the light incident angle on the device. Moreover, a liquid passivation layer is introduced to achieve stable and reversible exchange between the memristor and WORM behaviors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>